A study on clinico-pathological analysis of hysterectomies - Sinhasane, Hema; GM, Nishty (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Routes for hysterectomy include abdominal, vaginal, laparoscopic, or combined approaches. Traditional abdominal hysterectomy (AH) is one of the most common gynaecological surgical procedures in the treatment of benign gynaecological diseases. However, AH as the most invasive procedure, is associated with some limitations such as abdominal trauma, intraoperative and postoperative complications, and slow postoperative recovery. Methods: All the patients attending Gynecology outpatient department with symptoms were assessed with history and clinical examination by the Consultant Gynecologist and investigated. Those requiring hysterectomy were analyzed by the Consultants for the approach depending on the indication for the surgery, nature of the disease and patient characteristics. Results: The most common indication for hysterectomy was prolapsed uterus (29.4%) followed by menstrual disorders (25.8%), leiomyoma (22.9%), and PID (12.3%). Conclusions: Hysterectomy is successful in relieving pain, carcinomas and obstetric complication.